Project-based learning for the development of soft skills in three academic schools - Romani-Pillpe, Guillermo (2023)
The present work investigates if project-based learning allows the development of soft skills in three academic schools of a university in Ica. To discover it, we worked with 71 students. These were divided into three groups: Primary Education School (32); School of Initial Education (22); School of Language and Literature (17). The first group did not receive any intervention program on project-based learning. The second experimental group received training in PBL; and the third experimental group received PBL training that allowed them to relate to soft skills. Three groups were given a Likert-type questionnaire. At the beginning —pretest—, and at the end —postest—. The results obtained by Kruskall Wallis, indicated that both experimental groups distinguished changes in relation to the control group. In conclusion, it is up to teachers to promote constant practice through active methodologies (ABP) for a better development of soft skills.